The Ambiguity of the 'Public Policy Clause in the Execution of Foreign Arbitration Awards in Indonesia - Ali Fikri, Ahmad Wildan (JUNCTO: Jurnal Ilmiah Hukum, 2025)
Arbitration has appeared as a leading forum in settlement dispute commercial international. stated that execution decision arbitration international can implemented if not contrary to public policy. Usage This clause gives rise to confusion in interpretation and become the cause failure execution decision arbitration foreign so that required study about what is the cause confusion? and how to execute it so still can implement? This research is research that uses method study law normative equipped with an approach legislation, comparison and approach conceptual work done in a way descriptive analytical in to study interpretation clause in regulation applicable legislation, cases that occur in various countries to compared to as well as concepts as solution. Research results state that uses This clause is contained in the AAPS Act 1999 and Article V of the New York Convention for limit implementation arbitration foreign. Decision arbitration foreign need acknowledged or ratified in the country were implementation execution. Public policy not only concerning interest individual or group just but more to objective together, interests general, or citizens in general. Rejection decision arbitration based on policy public need condition outside usual, namely " threat" real and serious to interest fundamental society." The situation This also happened in India, the European Union and Russia with various each solution. In order not to be ambiguous, Execution decision should load certainty just law, principle consensualism, fair and equal treatment, and violation characteristic final and binding decision. It is hoped that this article will come as reflection stakeholders’ policy for escort 'public policy' clause general ' so as not to obstacle for execution decision arbitration foreign.